IMPLEMENTATION EVALUATION OF THE STUDENT'S FIELD WORK PRACTICE PROGRAM IN THE VOCATIONAL SCHOOL 7 SERANG, USING THE COUNTENANCE STAKE MODEL - Yulianti, Dinda; Abizar, Haris; Abdillah, Hamid (Department of Mechanical Engineering Education, 2024)
The Field Work Practice Program is prepared by educational institutions and the industrial sector. This program is designed to contribute to the vocational school students' development. However, the implementation of Field Work Practices faces several problems that affect its effectiveness. This research was conducted to evaluate the Field Work Practices in the Department of Mechanical Engineering at State Vocational High School 7 Serang City in terms of the Preparation (Antecedent), Implementation (Transaction), and Results (Outcomes) stages. This research is a mixed method evaluative research (combination method), using an explanatory sequential approach. In this study, the student population was 68, so the sample size was 68 students and 4 teachers. All Field Work Practice Student preparation consists of Regular Learning and debriefing which resulted in 82% being in the very good category, then 68 students found that 84.02% were in the very good category. The entire implementation of Field Work Practice (Transaction) which consists of the Work Orientation and Competency Period, from the teacher's perception, obtained results of 84% in the very good category and from student perception 33% in the sufficient category. After implementing the Field Work Practice (Outcomes) there was a School Assessment and Industrial Assessment, from the teacher's perception the results were 88% in the good category and from the students' perceptions the results were 81% in the sufficient category. All indicators of the Field Work Practice preparation stages (Antecedents) are considered sufficient. The implementation stages (Transactions) are considered good, but there are still shortcomings where when carrying out Field Work Practice students are still not disciplined which causes the school to be blacklisted for more than 1 year from several industries. The results of the Field Work Practice (Outcomes) evaluation were declared good.